A simple geometrical path towards hybrid orbitals - Nacbar, Denis Rafael; Ribeiro, Allan Victor [UNESP]; Bruno-Alfonso, Alexys [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
It is shown that the standard sp(n) hybrid orbitals are orthogonal orbitals that minimize the total quadratic spread. This is done in a concise way that may improve the understanding of hybrid orbitals. The fact that maximally localized Wannier functions of crystalline materials may resemble hybrid orbitals is discussed.
Keywords: Hybrid orbitals; Localization; Wannier functions